2006
DOI: 10.3892/ijmm.18.6.1073
|View full text |Cite
|
Sign up to set email alerts
|

Comano's (Trentino) thermal water interferes with interleukin-6 production and secretion and with cytokeratin-16 expression by cultured human psoriatic keratinocytes: Further potential mechanisms of its anti-psoriatic action

Abstract: Abstract. Thermal balneotherapy with Comano's spa water (CW; Trentino, Italy) is used for psoriasis and other skin disorders but its mechanisms of action are mostly unknown. Previously, we showed that CW can interfere with the expression and secretion of various VEGF-A isoforms by cultured human psoriatic epidermal keratinocytes. In this study, confluent cultures of IL-6-hypersecreting keratinocytes isolated from 6 psoriatic patients were exposed for 11-15 days to DMEM, the chemicals of which had been dissolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…Here, we will show that the addition of CW (in total or partial stead of DW) to the growth medium remarkably hinders the hyper-expression of TNF-· and the heightened production and release of IL-8 on the part of the psoriatic keratinocytes. Therefore, our previous (49,50) and present findings are consistent with CW being endowed with a complex phenotype-and cytokine/chemokine-regulating potential that translates into valuable anti-psoriatic therapeutic benefits.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…Here, we will show that the addition of CW (in total or partial stead of DW) to the growth medium remarkably hinders the hyper-expression of TNF-· and the heightened production and release of IL-8 on the part of the psoriatic keratinocytes. Therefore, our previous (49,50) and present findings are consistent with CW being endowed with a complex phenotype-and cytokine/chemokine-regulating potential that translates into valuable anti-psoriatic therapeutic benefits.…”
Section: Introductionsupporting
confidence: 73%
“…In conclusion, our previous (49,50) and present observations support the view that CW balneotherapy may elicit its beneficial effects by interfering with an improper local production and secretion of several chemokines and cytokines, including TNF-·, IL-8, IL-6, and various VEGF-A isoforms, and by attenuating some facets, such as CK-16 expression, of the psoriatic phenotype, which altogether locally underlie the epidermal hyperplasia and dermal neoangiogenesis, inflammation, and leukocyte infiltration phenomena proper of psoriatic illness.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Despite the fact that balneotherapy has been used for a long time with apparent good clinical results, the mechanism of action is unknown. Recent studies have shown that Comano water can effectively reduce the production of factors relevant to the pathogenesis of psoriasis (15)(16)(17) and that balneotherapy can represent an interesting adjuvant or alternative therapy for psoriasis patients willing to discontinue pharmacologic therapy (18).…”
Section: Introductionmentioning
confidence: 99%